Characterization of the first intragenic SATB2 duplication in a girl with intellectual disability, nearly absent speech and suspected hypodontia - Kaiser, Ann-Sophie; Maas, Bianca; Wolff, Anna; Sutter, Christian; Janssen, Johannes W. G.; Hinderhofer, Katrin; Moog, Ute (European journal of human genetics, 2015)
SATB2, a gene encoding a highly conserved DNA-binding protein, is known to have an important role in craniofacial and neuronal development. Only a few patients with SATB2 variants have been described so far. Recently, Döcker et al provided a summary of these patients and delineated the SAS (SATB2-associated syndrome). We here report on a girl with intellectual disability, nearly absent speech and suspected hypodontia who was shown to carry an intragenic SATB2 tandem duplication hypothesized to lead to haploinsufficiency of SATB2. Preliminary information on this patient had already been included in the article by Döcker et al. We want to give a detailed description of the patient’s phenotype and genotype, providing further insight into the spectrum of the molecular mechanisms leading to SAS.
Published online 13 August 2014
Gesehen am 16.06.2020